2011
DOI: 10.1542/peds.2010-2833
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Amplitude-Integrated EEGs in Infants From Preterm to 3.5 Months of Age

Abstract: Reference values of aEEG amplitudes were obtained for infants with a wide range of PMAs and constituted the basis for the quantitative assessment of aEEG changes with maturation in neonates and young infants. The normative amplitudes of aEEG margins, especially of the lower margin in quiet sleep, are recommended as a source of reference data for the identification of potentially abnormal aEEG results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…The increasing adoption of the aEEG method in the neonatal intensive care unit is reflected by the growing number of studies published during the past decade, although these still do not match the knowledge that was gained in term-born infants over the same period of time (8)(9)(10). Efforts have been made to define normative values and changes in aEEG parameters with respect to gestational age (GA) and postmenstrual age (PMA) (11)(12)(13)(14)(15), and recently, integrative studies correlating aEEG with various clinical parameters have been published (16)(17)(18). These examples demonstrate that the concept of aEEG monitoring can be very useful in preterm infants.…”
mentioning
confidence: 99%
“…The increasing adoption of the aEEG method in the neonatal intensive care unit is reflected by the growing number of studies published during the past decade, although these still do not match the knowledge that was gained in term-born infants over the same period of time (8)(9)(10). Efforts have been made to define normative values and changes in aEEG parameters with respect to gestational age (GA) and postmenstrual age (PMA) (11)(12)(13)(14)(15), and recently, integrative studies correlating aEEG with various clinical parameters have been published (16)(17)(18). These examples demonstrate that the concept of aEEG monitoring can be very useful in preterm infants.…”
mentioning
confidence: 99%
“…The main reason to select nonparametric measures such as the median and percentiles is that they are noise-proof and, thus, insensitive to outliers with extremely high amplitudes. Moreover, the amplitude of the aEEG is not normally distributed, such that nonparametric statistics are more suitable [3,5,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed algorithm has been employed to analyze aEEG data from a large population of infants, and a related article was published in a top journal of pediatrics [20]. Although our clinical and research practice has verified that the algorithm and the calculation parameters shown in Figure 4 are robust in various environment, some of the parameters may need to be adapted using a calibrated method (i.e., as shown in Section 3) if raw EEG data are collected under very special circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quantitative analyses, we used the following method, modified from the previously reported method of Zhang et al (20). We outputted the UMA and the LMA data from all seven channels for the entire record as a text file from the NicoletOne Monitor, with a time resolution of 1 s. Then the data were divided into epochs of 15 s, and the maximum of UMA and minimum of LMA were extracted in accordance with the standard clinical aEEG trace.…”
Section: Aeeg Assessmentsmentioning
confidence: 99%